Talking about a revolution : the languages of educational reform - Cossentino, Jacqueline, 1964- (SUNY series, restructuring and school change., 2004)
"Talking about a Revolution tells the story of school reform from the perspective of teachers engaged in it, illuminating the complexity of teachers' roles in transforming policy into practice. Al, Brian, and Camille teach at a large, comprehensive high school in a suburb of a major mid-western city. They use the languages of educational reform to inspire new ways to think about teaching, to shield themselves from the confusion of contradictory understandings of reform, and to construct a shared understanding of what reformed teaching might mean."--Jacket